2014
DOI: 10.30750/ijpbr.2.4.8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and perception of HIV / AIDS among married women

Abstract: Background:In India, the rising prevalence of HIV among pregnant women is of great concern. Pregnant women are much receptive on health matters. So, it is important to assess their knowledge, attitude and perception regarding HIV/AIDS. Aims: To know the knowledge and to know the various factors influencing the knowledge regarding HIV/AIDS in married women. Setting and design: The present community based cross sectional study was carried out in rural health training centre Ukkali, which belongs to department of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…8 In our study 58% women believed that infected blood transfusion is the mode of transmission of HIV which was more than 90% in the study conducted by Basu et al 6 In the study conducted by Biradar et al 20.4% participants told that HIV/AIDS spreads through unprotected sex, 17.0% participants told that HIV/AIDS spreads through blood products and 6.3% participants told that HIV/AIDS spreads through mother to child. 4 Nearly half of the study participants according to Juliet Sylvia et al had misconceptions regarding routes of transmission such as mosquito bites and sharing food similar to that found in our study where 49% study participants reported that HIV/AIDS can be transmitted by mosquito bite and hugging the infected person. 8 As far as the knowledge about the place of getting tested for HIV, 54% women said they don't have knowledge about the place for testing the HIV while 29% of woman said the test could be done in government as well as private hospitals.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…8 In our study 58% women believed that infected blood transfusion is the mode of transmission of HIV which was more than 90% in the study conducted by Basu et al 6 In the study conducted by Biradar et al 20.4% participants told that HIV/AIDS spreads through unprotected sex, 17.0% participants told that HIV/AIDS spreads through blood products and 6.3% participants told that HIV/AIDS spreads through mother to child. 4 Nearly half of the study participants according to Juliet Sylvia et al had misconceptions regarding routes of transmission such as mosquito bites and sharing food similar to that found in our study where 49% study participants reported that HIV/AIDS can be transmitted by mosquito bite and hugging the infected person. 8 As far as the knowledge about the place of getting tested for HIV, 54% women said they don't have knowledge about the place for testing the HIV while 29% of woman said the test could be done in government as well as private hospitals.…”
Section: Discussionsupporting
confidence: 78%
“…Biradar et al have reported that among their study population majority (77.5%) had heard about HIV/AIDS. 4 In the study conducted by Chatterjee et al 5 Only 236 (67%) of the 350 women interviewed had heard of AIDS and Basu et al had reported that 633 (100%) of the study population had heard about HIV/AIDS. 6 Ye et al 91.6% reported that they had ever heard of HIV/AIDS obtained from various sources.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Most of the peoples in both (97.5%) have a good level of knowledge. [7] More than 97% of peoples know HIV might be spread via transmitted from mother to child [52±48.08] [8] , transmitted by sharing a needle or a syringe [52.5±48.79] [9] and transmitted by blood transfusion [53±49.5; p=0000]. A similar result was reported by Kiran et al [10] study in whom, 94.12% were aware regarding contaminated needles and syringes, 95.09% on blood transfusion.…”
Section: Discussionmentioning
confidence: 58%
“…In this line, the findings of various studies had revealed that the majority of women did not know about HIV/AIDS. [ 18 19 ] In this respect, in the study by Haroun et al ., 61% of university students had moderate levels of knowledge concerning the HIV/AIDS epidemic. [ 20 ] These findings were strong evidence that raising awareness of HIV/AIDS needed continuing education, highly supported by national media, the government, medical staff, as well as affiliated medical teams.…”
Section: Discussionmentioning
confidence: 99%